Design of Enhanced Method for Detection and Removal a Shadow from Video Frames - Kalas, MS; Sonawane, BD (International Journal of Computer Sciences and Engineering, 2020)
It is very difficult to remove the shadow from video frames or an image, so we need to find the solution for this. Here we did survey for the required information. Due to the excessive-order textural material within the video frame directly removed the intensity area of the shadow frame is difficult. There are various filters for image segmentation, here we used a mean-shift filter to remove a noise and smoothening of video frame. A region growing algorithm is used for the shadow detection through the user. Using 3D modelling and inpainting, an intensity surface of illumination in the shadow region can be received primarily based on that similar to the equal texture inside the non-shadow one. In comparison to the alternative strategies, this is a user-assisted method that solves a shadow detection problem and applies to the shadow, consisting of various types of textures. In future, when we apply this system for video, this process is well suitable for the less duration video because, for each frame the user gives some important information to the system.